Nanoscale Strain Fields Research of Boundaries between B2 Matrix and G.P. Zone in Ni-Ti Alloy Thin Films - Shilei Zhao; Chunwang Zhao (The Scientific World Journal)
Ti-47at.%Ni alloy films were prepared by magnetron sputtering followed by 460°C for 40 minutes heat-treatment. The strain fields between B2 phase matrix and G.P. zone were mapped by a combination of high-resolution transmission electron microscopy and geometric phase analysis method. It was found that there is a compressive strain region parallel to the longitudinal axis of G.P. zone with 2 nm in width, −2.2% in average strain at the boundaries between B2 phase and G.P. zone.